Drug-to-Antibody Ratio Estimation via Proteoform Peak Integration in the Analysis of Antibody-Oligonucleotide Conjugates with Orbitrap Fourier Transform Mass Spectrometry - Nagornov Konstantin O.; Gasilova Natalia; Kozhinov Anton N.; Virta Pasi; Holm Patrik; Menin Laure; Nesatyy Victor J; Tsybin Yury O. (AMER CHEMICAL SOC, 2022)
The therapeutic efficacy and pharmacokinetics of antibody-drug conjugates (ADCs) in general, and antibody-oligonucleotide conjugates (AOCs) in particular, depend on the drug-to-antibody ratio (DAR) distribution and average value. The DAR is considered a critical quality attribute, and information pertaining to it needs to be gathered during ADC/AOC development, production, and storage. However, because of the high structural complexity of ADC/AOC samples, particularly in the initial drug-development stages, the application of the current state-of-the-art mass spectrometric approaches can be limited for DAR analysis. Here, we demonstrate a novel approach for the analysis of complex ADC/AOC samples, following native size-exclusion chromatography Orbitrap Fourier transform mass spectrometry (FTMS). The approach is based on the integration of the proteoform-level mass spectral peaks in order to provide an estimate of the DAR distribution and its average value with less than 10% error. The peak integration is performed via a truncation of the Orbitrap's unreduced time-domain ion signals (transients) before mass spectra generation via FT processing. Transient recording and processing are undertaken using an external data acquisition system, FTMS Booster X2, coupled to a Q Exactive HF Orbitrap FTMS instrument. This approach has been applied to the analysis of whole and subunit-level trastuzumab conjugates with oligonucleotides. The obtained results indicate that ADC/AOC sample purification or simplification procedures, for example, deglycosylation, could be omitted or minimized prior to the DAR analysis, streamlining the drug-development process.